Therapeutic effectiveness of Hydroxyapatite Nanoparticles and Pulsed Electromagnetic Field in Osteoporosis and Cancer - Prakash, Divya; Chauhan, Shikha S; Behari, Jitendra (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2019)
The emergence of nanotechnology has had a profound effect on many areas of healthcare and scientific research. Several studies reported the importance Hydroxyapetite Nanoparticles in the biomedical field in general, and in emerging areas such as implants, drug delivery, cancer, composites, coatings, and ceramic materials in particular. On the other hand, low level Pulsed electromagnetic field (PEMF) therapy presents several potential advantages including non-invasiveness, safety, highly influential in the fracture repair process, lack of toxicity for non-cancerous cells, and the possibility of being combined with other available therapies. It has also been observed that the combined effect of these two can accelerate the osteognic and anticancer activity in the osteoporotic and carcinoma cell lines respectively. The objective of this review is to provide a broad recount of the applications of PEMFs and Hydroxyapatite nanoparticles in osteoporosis and cancer and to then demonstrate what is further required for enhanced therapeutic outcomes.